Uma nova visão fático-social da posse - Bolonhini Junior, Roberto (2013)
This thesis demonstrates the social function of ownership from a new perspective phatic-social. At first we try to study the essential elements possessory where the phenomenon was structured throughout history; later, we do a study of the Tridimensional Theory of Law by Miguel Reale at the vision of Maria Helena Diniz, as well as the principle of human dignity enshrined in the charter. Then, the possession is studied socially and economically in the theories of Antonio Hernandez Gil, Perozzi and Saleilles comparing these scholars thought the thoughts of Jhering and Savigny. After this study dogmatic, is set to address the issue possessory actually factual-evaluative Brazilian and necessity of pursuing a real possession qualified for their functionalization, we emphasize the invasions and occupations of areas were not fulfill its function, made by popular movements in order civil disobedience and fulfill the social function of ownership; criticizes also the structure agrarian-urban Brazilian real estate, which favors the few over the many as a legacy of the colonial structure of exploitation, it is also a comparative study with alien legislation, demonstrating the adoption of constitutions in social function of property, but also the constitutional legislation which regulates the possession. We suggest a new theory, called the theory of social consciousness and their reflections on possessory title, lege ferenda suggestions are made, as well as changes in Brazilian law, thus seeking a new way of exercising possessory social function, unlike than was previously proposed by the doctrine